The evaluation of the reliability and validity properties of the Greek version of the xerostomia questionnaire (ΧQ) - Charalambous, Melanie; Papakyriacou, Christiana; Tsitsi, Theologia; Katodritis, Nicos; Vomvas, Dimitrios; Charalambous, Andreas (My University, 2021)
Purpose: Xerostomia is one of the multidimensional effects of cancer therapy that can impact on patients’ quality of life. This study aims to evaluate the reliability and validity properties of the xerostomia questionnaire. Methods: The data were retrieved from a randomized, interventional and longitudinal follow-up study of 72 head and neck cancer patients on active oral radiotherapy. Data were retrieved by the Xerostomia Questionnaire, the EORTC-QLQ C30 and EORT QLQ HN35. Data analyzes included intrinsic credibility of affinity Cronbach alpha factor, which is related to validity and cross-sectional validity. Results: The Cronbach's alpha index of the Greek version of the questionnaire was high. Explicitly, the total scale of the questionnaire had an α = 0.97, and the individual dimensions - Degree of dryness and the quality of life had an alpha of 0.97 and 0.98 respectively. The xerostomia dimension of the questionnaire has a high positive correlation with QLQ C30 overall (r = 0.61, p < 0.001), and with the HN35 xerostomia dimension (r = 0.63, p < 0.001) which demonstrate its' concurrent validity. The dimensions of the xerostomia questionnaire were highly correlated with the EORTC-QLQ C30 dimensions which supports its' predictive validity. The level of xerostomia and the quality of life varied according to the level of pain of the patients (p < 0.001) that support the cross-sectional validity of the questionnaire. Conclusion: The Greek version of the xerostomia questionnaire is a reliable and valid tool for use in head and neck cancer patients on active oral radiotherapy.
Keywords: Chemotherapy; Head and neck cancer; Quality of life; Radiotherapy; Xerostomia